The Teacher Recruitment and Deployment in Pakistani Private Schools - Ahmed, Nadeem (Studies in Learning and Teaching, 2025)
Teacher recruitment and deployment is one of the most essential ingredients of the school and teaching-learning process. Therefore, schools must recruit and deploy qualified, skilled, and professional teachers to satisfy learners’ educational requirements. The research aimed to examine the process and type of teacher hired in Pakistani private schools to teach learners. A phenomenological approach of qualitative research was employed to conduct the study. The purposive sampling method was utilized to undertake the research. Two focus groups discussion and six individual face-to-face interviews were conducted in two different private schools. It was found that teacher recruitment and deployment in private schools is a serious concern that needs to be addressed. Based on the findings, most middle-class private schools are facing a challenge to attract, recruit, and retain qualified teachers. The intention to gain maximum revenue impels these individual-owned business enterprise private schools to recruit under-qualified females on lower salaries. Moreover, non-availability and not-in-practice of the recruitment policies, procedures, and yardsticks are also reasons for under-qualified teachers’ recruitment. It is thus necessary for private schools to recruit qualified teachers for better teaching-learning.